El proyector digital como recurso didáctico para el aprendizaje de la línea recta en los estudiantes del primer año, del bachillerato general unificado, paralelo A, de la unidad educativa anexa a la Universidad Nacional de Loja, de la ciudad de Loja, periodo 2013 – 2014 - Calva Alvarez, Luis Vinicio (2015)
The research is titled THE DIGITAL PROJECTOR AS TEACHING LEARNING RESOURCE FOR STRAIGHT LINE IN FIRST YEAR STUDENTS, THE BACHELOR GENERAL UNIFIED, PARALLEL A, OF THE UNIDAD EDUCATIVA ANEXA A LA UNIVERSIDAD NACIONAL DE LOJA CITY OF LOJA, PERIOD 2013-2014. The aim of the investigation was to use the digital projector as didactic resource to improve the learning of the straight line. The methods applied in research are in order as follows: deductive, analytical - synthetic, scientific and quantitative - qualitative. The research process was structured based on a diagnosis, to study and identify problems that influence learning; to then plan the pertinent solution to offset the found difficulties; Apply the alternative of the investigation leading to achieve the objectives set, and perform the valuation through a technique of contrast quantitative and qualitative, Wilcoxon rank sign, which supports the effectiveness of the use of digital projector to enhance the learning of the straight line. The principal finding that it is considered to be they are the lacks or cognitive present needs in the learning of the straight line can be reduced with the application of digital projector as a teaching resource in learning the straight line.